TELER Performance as Real-Time Intrusion Detection and Threat Alert Based on Web Log-In Detecting Directory Bruteforce Attacks on Websites - Darmawan, Rio; Zen, Bita Parga; Kisworini, Rianti Yunita (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2023)
TELER is a real-time intrusion detection and weblog-based alerting tool that runs on the terminal. TELER is designed to be a fast terminal-based threat analyzer. The IDS (intrusion detection system) is needed to help web administrators secure their servers. This study aims to test the TELER performance as real-time intrusion detection and threat alert. This study tries to implement an open-source application called TELER based on Golang. The IDS testing method on the web server this time uses directory brute force with the result that TELER can detect an attack and provide prompt notification to the web administrator when an attack occurs on the web server. The result of this study shows that the TELER successfully sent notifications to the Telegram, Discord, and Slack applications when an attack or intrusion occurs. Based on the experiments conducted in this study, Slack is the most effective application for receiving directory brute-force attack notifications. The average time for Slack to receive attack information is 0.03 seconds. TELER was successfully proven to detect cyberattacks.